Encyclopedia of toxicology - Wexler, Philip, 1950-; Anderson, Bruce D. (Gale virtual reference library, 2005)
Provides a comprehensive survey of toxicology. Presents entries devoted to key concepts and specific chemicals. Also includes articles that focus on the societal implications of toxicological knowledge.